Будівництво помешкань для сільських вчителів (на основі архівних документів) - Годованська, Оксана; Годованський, Олег; Hodovanska, Oksana; Hodovanskyi, Oleh (Видавництво Львівської політехніки, 2020)
У статті опрацьовано архівні документи про будівництво житлових будинків для сільських вчителів. Незважаючи на те, що в українській гуманітаристиці поширеними є дослідження повсякденного трибу життя різних соціальних прошарків радянського суспільства, про житлово-побутові умови сільських вчителів немає окремих наукових праць. Мета статті полягає у з’ясуванні механізму забезпечення житлом сільських вчителів на основі офіційних документів радянських органів влади, насамперед, наказів і постанов міністерства освіти УРСР, розпоряджень Львівського обласного відділу народної освіти та збережених планів забудови.

The article examines archival documents about the construction of residential buildings of village teachers. In Ukrainian science there are many studies about the everyday life of different social strata of soviet society. But there are not separate scientific papers about the residential apartments and the household living conditions of village teachers. The focus of this study is the everyday life of soviet era teachers in the villages of Halychyna. The purpose of the article is to study the mechanism of receiving residential buildings of village teachers. The basis for the study of this question is the official documents of the Soviet state – are the orders and resolutions of the Ministry of Education of the of Soviet Ukraine and the instructions of the Lviv Regional Department of Public Education, and plans for the construction of residential buildings. These documents are in the Lviv Regional Archive. The soviet period, with its totalitarian nature, was also by modernization project to Ukraine. At the turn of the 1950–1960-ies of the ХXth century attention has increased of the Soviet state to the social needs of the population. The Soviet state built and implemented a whole system of political and social paternalism to its citizens. Soviet teachers were no exception to this system. First of all, village teachers received additional benefits and surcharges. The analysis of archival documents indicates that there is a clear vertical power and the built system of social paternalism over teachers. Always, homes for village teachers were built by an approved template plan, always close to school. Priority in construction plans was given to functional purpose. The construction residential building to village teachers was planned in conjunction with the construction of a new village school on one site. The construction residential building to village teachers was with a utilitarian approach, with restrictions on comfortable living conditions. For example, install a telephone line and radio communication in the teachers’ homes, but, according to the plan, placed the furnace heating.
The residential buildings of village teachers (on the basis of archival documents)
Keywords: сільські вчителі; житло; повсякдення; Галичина; УРСР; village teachers; residential building; everyday life; Halychyna; Soviet Ukraine; [930.2; 69; 728.6; 37.011.3-051](477.83/.86-22)"195/196"(093.2)